Thermoplastic composition based on recycled polypropylene

JP7651702B2Active Publication Date: 2025-03-26LOREAL SA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023535552
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-10
Filing Date
2021-12-10
Publication Date
2025-03-26
Estimated Expiration
2041-12-10

AI Technical Summary

Benefits of technology

を誘導することを教示している。しかしながら、この文献は、再生hPPに由来する組成物の射出成形によって得られる物品の場合に、copoPPで作製された物品の性能品質を得ることに関するものでは決してない。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651702000001
    Figure 0007651702000001
  • Figure 0007651702000002
    Figure 0007651702000002
  • Figure 0007651702000003
    Figure 0007651702000003
Patent Text Reader

Abstract

The present invention relates to a thermoplastic composition comprising at least (a) recycled homopolypropylene (hPP) having a specific melt flow index and (b) a mixture of specific olefins in an amount of 2% to 25% by weight, relative to the total weight of the composition. A further object is a process for the preparation of molded articles starting from such a composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic composition comprising at least one recycled polymer. [Background technology]

[0002] In order to conserve natural resources, today there is a demand to regenerate packaging materials for consumer products, for example polymers of packaging for personal hygiene care products, such as shampoo and cleansing gel bottles, and packaging for detergent-type products for laundry and household cleaning, in order to produce new packaging by injection moulding these used materials. This regeneration process has already been considered for the grades of polypropylene homopolymer "hPP" resulting from mechanical recycling and will be considered in the next few years for the grades of hPP produced by chemical recycling.

[0003] However, to the best of the inventors' knowledge, there is no satisfactory recycled polypropylene copolymer grade "copoPP". In fact, copoPP currently constitutes a polymeric material that is particularly valued for packaging products due to its good mechanical quality and transparency. US Patent No. 8,426,521 teaches that the addition of a mixture of specific olefins to a certain grade of recycled polypropylene induces beneficial effects on the mechanical properties of this polypropylene. However, this document is never concerned with obtaining the performance qualities of articles made with copoPP in the case of articles obtained by injection molding of a composition derived from recycled hPP.

[0004] As a result, it would be clearly economically and environmentally advantageous to have available articles made with recycled hPP that are endowed with the performance qualities of articles made with copoPP in terms of clarity, impact strength and abrasion resistance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] U.S. Patent No. 8,426,521 [Patent Document 2] International Publication No. 2017 / 003800 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention is particularly directed to meeting this need. [Means for solving the problem]

[0007] Thus, the present invention mainly comprises: (a) recycled homopolypropylene, hPP, having a melt flow index of greater than 20 grams per 10 minutes (20 g / 10 min), measured at 230° C. under a load of 2.16 kg according to standard ASTM D1238; and (b)(i) a copolymer having at least 75% by weight of propylene-derived units and 10% to approximately 25% by weight of linear or branched C units, referred to as a “first copolymer” 2 Or C 4~10 Propylene / C having alkenyl units 2 Or C 4~10 α-olefin copolymers, and (ii) A homogeneous linear or branched ethylene / C copolymer, referred to as the “second copolymer” 4~10 Alpha-Olefin Copolymer A thermoplastic composition comprising at least 2% by weight to approximately 25% by weight of a mixture of olefins, based on the total weight of the composition, It relates to a thermoplastic composition in which the "second copolymer / first copolymer" mass ratio is between 0.1 and 0.4, in particular between 0.15 and 0.30, and in fact even about 0.2 or even equal to 0.2.

[0008] It should be noted that the ASTM D1238 standard and the ISO 1133 standard are for those skilled in the art and are two standards that derive the same value of the Melt Flow Index.

[0009] In particular, the first copolymer is a copolymer of propylene and ethylene.

[0010] In particular, the second copolymer is a copolymer of propylene and 1-octene.

[0011] In particular, the thermoplastic composition according to the present invention may further comprise at least one clarifying additive.

[0012] According to another of its aspects, in combination with the previous ones, the present invention relates to a molded article, in particular an injection molded article, which is preferably transparent and which is obtained by molding, in particular by injection molding, a composition as defined above and described in detail below, in a mold.

[0013] Such moulded articles, in particular injection moulded articles, may be selected from the group consisting of capsules, seals, reducers, caps (e.g. sealing caps for containers or bottles) and bands, containers, bottles, preforms for bottles or any other moulded article, in particular injection moulded article, e.g. used in conjunction with a bottle or constituting a container itself, e.g. a case, in particular for personal care and / or make-up.

[0014] Such articles can, of course, be dedicated to a wide variety of uses.

[0015] According to yet another of its aspects, in combination with the preceding, the present invention provides a method for the manufacture of a shaped article, comprising the steps of: - making available a composition as defined above or preparing such a composition, - molding said composition in a mold having the shape of said article, in particular by injection molding, and - recovering said moulded article, in particular said injection moulded article. The present invention relates to a method comprising at least the steps of:

[0016] Where the method includes the step of preparing the composition, this step may include: - selection of the compounds of the composition, which at least comprises homopolypropylene, hPP, and the mixture of said olefins, - these preparations in their respective proportions, and - Mixing these together using a mixer may include.

[0017] The method can include, prior to the moulding step, in particular the injection moulding step, a test step consisting in carrying out, in said mould, a moulding step, in particular by injection moulding, using at least one test composition based on a polypropylene copolymer, for example based on a polypropylene copolymer having the trade name Moplen RP348R-Basell, having an MFI of 25 g / 10 min and sold by the company LyondellBasell.

[0018] In this case, the method may include adjusting the parameters of the molding, in particular the injection molding, of the article using the parameters used for the test phase.

[0019] The manufacturing method according to the invention can also include a step of blow moulding a moulded article, in particular an injection moulded article, in which case the moulding, in particular injection moulding, step and the blow moulding step can be carried out successively, with a short interval between them, or with a long interval between them, in which case changes in the machines and / or the storage of the preforms can be envisaged between the two steps.

[0020] Other techniques for producing articles from the compositions according to the invention include, in addition to injection molding, for example, thermoforming, extrusion, extrusion / blow molding, compression, rotational molding, additive manufacturing, and other techniques known for forming polymers, in which case the molded article would then not be an injection molded article, but rather a thermoformed, extrusion, extrusion / blow molding, compression, rotational molding, or 3D printed article, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] As will become apparent from the examples below, the inventors have discovered that the combination of a specific mixture of two specific copolymers with a specific grade of recycled hPP makes it possible to impart performance qualities to the resulting thermoplastic compositions that are comparable to those of thermoplastic compositions formed from polypropylene copolymers. Contrary to all expectations, the qualities in terms of mechanical properties and transparency of thermoplastic articles produced from these two types of compositions turn out to be coordinated.

[0022] As specified above, the thermoplastic composition according to the invention comprises: (a) recycled homopolypropylene, hPP, having a melt flow index of greater than 20 grams per 10 minutes (20 g / 10 min), measured at 230° C. under a load of 2.16 kg according to standard ASTM D1238; and (b) (i) propylene / C in the applicable (ii) / (i) mass ratio as defined above; 2 Or C 4~10 (ii) a first copolymer of an α-olefin, and (iii) a homogeneous ethylene / C 4~10 A mixture of olefins, comprising at least a second copolymer of an α-olefin, in an amount of from 2% to approximately 25% by weight, based on the total weight of the composition. At least

[0023] Recycled hPP homopolypropylene The polypropylene homopolymer, hPP, contemplated by this invention is a recycled homopolymer.

[0024] Within the meaning of the present invention, recycled homopolypropylene is a homopolymer of plastic homopolypropylene waste obtained from reconversion by mechanical or chemical recycling, as described, for example, in WO 2017 / 003800.

[0025] The polypropylene homopolymers considered according to the invention are characterized in particular by having a melt flow index determined appropriately, i.e. greater than 20 g / 10 min, preferably at least equal to 25 g / 10 min, as determined according to ASTM D1238 (conditions 230° C., mass of 2.16 kg).

[0026] The polypropylene homopolymers considered according to the invention additionally advantageously have a melting point varying between 130 and 170° C. (measured by DSC according to ISO 11357-3: 1999). The compositions according to the invention generally comprise at least 75% by weight, indeed even 80% to 95% by weight, of recycled hPP relative to the total weight.

[0027] Particularly suitable as recycled hPP is polypropylene available from Total under the trade names PPH 9040 and PPH 10 042.

[0028] Olefin Mixture The compositions according to the present invention may also contain a mixture of olefins.

[0029] As described in detail below, this mixture of olefins comprises, and in fact may even consist of, two copolymers, one of which is propylene / C 2 Or C 4~10 α-olefin copolymer and the other is homogeneous ethylene / C 4~10 It is an alpha-olefin copolymer.

[0030] Propylene / Olefin Copolymer This copolymer, also referred to as the "first copolymer" according to the present invention, can be described as an elastomer in terms of its elastic properties.

[0031] The weight average molecular weight (M w ) can in particular vary from 165,000 g / mol to approximately 360,000 g / mol.

[0032] The first copolymer contemplated by the present invention may have a melt flow index (according to ASTM D1238, conditions 230° C., 2.16 kg) ranging from 1.5 grams / 10 minutes to 500 grams / 10 minutes, preferably from 2 grams / 10 minutes to 100 grams / 10 minutes.

[0033] The first copolymer according to the present invention also has a viscosity of 0.50 to 0.95 g / cm 3 within the range of 0.75 to 0.90 g / cm 3 The density may be in the range of 0.1 to 1.0 μm.

[0034] As specified above, the first copolymer based on polypropylene suitable for the present invention comprises at least 75% by weight, preferably at least 80% by weight and more preferentially at least 83% by weight, of units deriving from propylene relative to the total weight.

[0035] Copolymers suitable for the present invention as the first copolymer further comprise from approximately 10% to approximately 25% by weight, preferably from 12% to approximately 20% by weight, for example from 13% to 16% by weight, indeed even approximately 15% by weight, of units derived from an α-olefin, relative to the total weight.

[0036] The expression "units derived from" is to be understood as describing not only olefinic units identified with themselves, but also related units having a replacement unit, such as a halogen atom, at one of the hydrogen atoms of the olefinic unit considered, as long as this unit does not affect the qualities desired according to the invention, namely mechanical strength and transparency. Preferably, these derived units are units identified with themselves, such as propylene units.

[0037] With respect to the "olefin" moiety, it is derived from an α-olefin, i.e., the olefin necessarily has a double bond at the α or primary position. The "olefin" moiety may be linear or branched, but is preferably linear.

[0038] Examples of linear α-olefins are ethylene, propylene, 1-butene and 1-decene. An example of a branched α-olefin is isobutylene.

[0039] Very particularly preferred are 2 , C 4 , C 6 and / or C. 8 An α-olefin, in particular ethylene and / or 1-butene, in particular ethylene.

[0040] Very particularly suitable for the present invention are propylene / ethylene copolymers, in particular those available under the trade name "Vistamaxx" from ExxonMobil Chemical Company, very particularly Vistamaxx 6202.

[0041] Homogeneous ethylene / α-olefin copolymer As will become apparent from the present description, these copolymers, also called "second copolymers" according to the invention, differ from the "first copolymers", in particular in that they lack units derived from propylene.

[0042] The second copolymer according to the invention is a plastomer: it should be recalled that a plastomer is a linear polymer which, in contrast to an elastomer, is capable of undergoing elastic deformation accompanied by permanent plastic deformation under the action of a stress.

[0043] The copolymer is made of ethylene and / or C 4 ~C 10 Copolymers are said to be homogeneous because the α-olefin derived entities are arranged in a random, alternating and / or statistical arrangement, as opposed to a block arrangement, and the copolymers are sometimes referred to as statistical.

[0044] Thus, the second copolymer according to the present invention contains a single amorphous phase and has a single Tg, which is intermediate between the Tg's exhibited by each of the corresponding homopolymers.

[0045] In particular, their glass transition temperature Tg (measured by DMTA in accordance with ISO 6721-7) is generally below -25°C, preferably below -30°C and more preferably below -35°C.

[0046] The second copolymer of the present invention is advantageously a very low density polyolefin, more preferably a very low density polyolefin polymerized using a single-site catalyst, preferably a metallocene.

[0047] In particular, the ethylene-based second copolymer has a viscosity of 0.860 to 0.915 g / cm 3 within the range of 0.860 to 0.910 g / cm 3 in the range of 0.86 to 0.905 g / cm 3 The density may be in the range of 0.1 to 1.0 μm.

[0048] The second copolymers according to the invention may have a melt flow index (according to ASTM D1238, conditions 230° C., 2.16 kg) of at least 0.5 g / 10 min, indeed even at least 1.0 g / 10 min. They may more particularly have a melt flow index of less than approximately 200 g / min, in particular between 2 and 15 g / 10 min.

[0049] The melting point (T m ) (measured by DSC according to ISO 11357-3:1999) are generally below 130° C., preferably below 120° C., more preferably below 110° C., and most preferably below 100° C. They are further generally above 80° C., preferably above 90° C.

[0050] Ethylene and C 4 ~C 10 The copolymers with α-olefins generally have an ethylene content of between 50% and 98% by weight, preferably between 55% and 90% by weight and more preferentially between 60% and 85% by weight.

[0051] Very particularly suitable for the present invention 4 ~C 10 The α-olefins are 1-butene, 1-hexene and / or 1-octene, preferably 1-butene and / or 1-octene, and more particularly 1-octene.

[0052] Preferably, a copolymer of ethylene and 1-octene is used.

[0053] Very particularly suitable for the present invention are ethylene copolymers, such as those sold under the trade name Queo 0203 by Borealis, under the trade name Engage or Affinity by Dow Chemical Corp (USA) or under the trade name Tafmer by Mitsui.

[0054] Alternatively, these ethylene-based copolymers can be prepared by known methods according to one- or two-stage polymerization processes, including solution polymerization, suspension polymerization, gas phase polymerization or a combination thereof, in the presence of suitable catalysts known to those skilled in the art, such as catalysts having vanadium oxide, or catalysts having single-site catalysts, such as metallocene catalysts, or catalysts having constrained geometry.

[0055] Preferably, these ethylene-based copolymers are prepared by a one- or two-stage solution polymerization process, in particular by a high-temperature solution polymerization process at temperatures above 100°C.

[0056] As specified above, the inventors have specifically found that combining these first and second copolymers according to the invention in specific ratios is crucial to obtain recycled hPP having unexpected mechanical performance qualities, and that outside these ratios is not achievable in other ways.

[0057] Thus, in the context of the present invention, recycled hPP is combined with a mixture of olefins containing these two copolymers in a second copolymer / first copolymer mass ratio between 0.1 and 0.4, in particular between 0.15 and 0.30, indeed even about 0.2 or equal to 0.2.

[0058] Of course, the composition according to the invention can contain two or more first copolymers and two or more second copolymers, in which case the aforementioned weight ratio is established by considering the sum of the amounts of the first copolymers in the sum of the amounts of the second copolymers.

[0059] The composition according to the invention may comprise from about 2% to about 25% by weight, preferably from about 5% to about 15% by weight, more preferably from about 8% to about 12% by weight of the mixture of olefins according to the invention, relative to the total weight.

[0060] Naturally, the amount of the mixture of olefins present in the composition according to the invention may be adjusted according to the possible end use envisaged for the composition.

[0061] For example, if the composition is intended to be injection molded to form a sealing cap for packaging, such as a shampoo packaging, the composition may contain more than 10% by weight of such mixtures relative to the total weight.

[0062] The mixture of first and second copolymers constituting the mixture of olefins according to the invention furthermore confers on the latter sufficient flowability to be compatible with injection moulding.

[0063] This is because an excessively viscous molten thermoplastic composition requires high pressure in the mold and does not flow well in the mold, whereas an excessively flowable molten thermoplastic composition can cause material penetration in the mold.

[0064] In addition, the high temperature flowability of the composition has an effect on the mechanical strength of the article obtained from the injection molding: the more flowable the material is, the more brittle it is, and conversely, if the material is too viscous, residual stresses in the parts may arise with a corresponding risk of failure.

[0065] Generally, the melt flow index of the composition is close to that of a polypropylene homopolymer, and therefore is as detailed above.

[0066] Other Additives in the Composition The composition according to the invention may further contain one or more additives conventionally considered in polymer compositions.

[0067] Thus, the composition according to the invention may contain at least one additive selected from antioxidants, heat stabilizers, UV stabilizers, flame retardants, antistatic agents, foaming agents, impact modifiers, compatibilizers, fillers, reinforcing fibers, optical brighteners and lubricants.

[0068] As specified above, the present invention is particularly directed to the development of injection molded articles having good transparency.

[0069] To this end, the composition advantageously further comprises a clarifying additive.

[0070] A clarifying additive is an additive whose function is to improve the transparency of the polymeric material it is incorporated in. The use of such additives is within the ability of one of ordinary skill in the art to select an additive in view of the chemical nature of the polymeric material being processed and the recommended directions for use for the selected clarifying additive.

[0071] Very particularly suitable for the present invention is the product sold under the name NX Ultraclear GP110B by the company Milliken.

[0072] The following examples are offered for illustrative purposes and are not intended to limit the scope of the invention.

[0073] material Homopolypropylene The test is carried out using the following recycled homopolypropylene. PPH9040 sold by Total with an MFI of 25g / 10min PPH10042 sold by Total with an MFI of 35g / 10min

[0074] Copolypropylene A polypropylene copolymer sold by LyondellBasell under the trade name Moplen RP348R-Basell, with an MFI of 25 g / 10 min, was used as a reference material for adjusting the molding protocol.

[0075] First copolymer of propylene It is available from ExxonMobil Chemical Company under the trade name Vistamaxx™ 6202, has an ethylene content of 15% by weight, a melt flow index (per ASTM D1238) of 18.0 grams / 10 minutes, and a melt flow index of 0.861 g / cm 3 It is a thermoplastic polymer of propylene / ethylene having a density (per ASTM D1505) of 1000 .mu.m.

[0076] A second copolymer of ethylene It is sold under the trade name Queo 0203 by Borealis and has a melt flow index (per ASTM D1238) of 3 grams / 10 minutes and a melt flow index of 0.912 g / cm 3 It is a copolymer of ethylene / octene having a density (per ASTM D1505) of 100%.

[0077] Tests were carried out on an injection moulding contoured to form a hinged, stopper-type service capsule for a shampoo bottle.

[0078] method The mechanical quality was evaluated by the following tests:

[0079] Crack Test A cracking solution is prepared containing 0.5%±0.05% (w / w) Trideceth-12 in deionized water. If necessary, dissolution is achieved by heating the water to approximately 35° C. Capsules to be monitored are placed in each bottle, and the bottles are placed upside down in a container filled with the cracking solution for 24 hours, then exposed to 55° C.+2° C. in an oven for 60 minutes.

[0080] The mechanical strength is indexed for a sample of more than 10 capsules as follows: +++None of the capsules showed any cracks ++Less than 10% of capsules exhibit cracks + More than 10% of capsules exhibit cracks

[0081] Leak Strength Test The test is carried out according to Method 1 or 2 detailed below, using a bottle filled with a coloured solution and sealed with a test capsule.

[0082] Method 1: A bottle sealed with a test capsule is placed in a vacuum chamber in an upside-down position and the pressure inside the chamber is adjusted to a value of -800 mbar for 15 seconds.

[0083] Method 2: The bottle sealed with the test capsule is placed in an oven at 45° C. in an upside-down position for 24 hours.

[0084] At the end of each of the two methods, a visual assessment is made to see if any leakage of the colored solution is observed.

[0085] The leak strength is indexed for a sample of over 10 bottles as follows: +++None of the bottles exhibited leakage ++Less than 10% of bottles exhibit leakage + More than 10% of the bottles exhibit leakage

[0086] Drop Test The test consists of filling a bottle with water to 100% of the commercialized containment volume and sealing it with a test capsule, then dropping it hinge-side down at an angle of 30° to the vertical from a height of 80 cm. If any degradation is observed in the capsule, it is considered to be non-compliant.

[0087] The mechanical strength in a single drop is indexed for a sample of more than 10 capsules as follows: +++ Fewer than 10% of capsules are broken ++Between 10% and 20% of the capsules are broken + More than 20% of capsules are broken

[0088] Durability Testing The test consists of manipulating the capsule for 50 openings and closings.

[0089] To do this, the test capsule is placed on a suitable adapter. The two end points, "open lid" and "closed lid", are monitored to be optimally adjusted. The counter is set to zero and each capsule is run for a minimum of 50 consecutive open / close operations. If any breakage occurs in the capsule under test, the article is considered defective.

[0090] Therefore, durability is indexed for a sample of over 10 capsules as follows: +++None of the capsules have broken hinges + Capsule hinge is broken

[0091] Assembly Test This test aims to establish the effectiveness of the assembly between the capsule and the bottle, in particular to evaluate the quality of screwing or snapping the capsule onto the bottle.

[0092] procedure Align the closure between the test capsule and the bottle with the dynamometer. Adjust the rate of displacement to 165±10 mm per minute. Activate the dynamometer and take the indicated force reading. Any assembly exhibiting values ​​outside the limits (minimum and maximum) indicated on the specification sheet is considered non-compliant.

[0093] The quality of the assembly is indexed for a sample of over 10 capsules as follows: +++None of the capsules are outside the specification range (min and max) ++ Fewer than 10% of capsules have values ​​below the minimum specification range + Fewer than 20% and more than 10% of capsules have values ​​below the minimum value of the specification range

[0094] Transparency Test A visual test is performed on the capsules and the observed clarity is compared to the clarity of a polypropylene copolymer having the trade name Moplen RP348R.

[0095] Equivalent transparency is indexed as +++.

[0096] Slightly detrimentally affected transparency is indexed as ++.

[0097] Translucent parts are indexed with +. EXAMPLES

[0098] Preparation of compositions and non-compliant compositions according to the present invention The components and respective amounts of the composition according to the present invention, designated No. 1, are detailed in Table 1 below.

[0099] Information is also provided on compositions designated Controls T1-T5, with composition T1 containing only propylene copolymer.

[0100] The mixture is prepared in a plastic bag for 5 minutes. For each sample, 20 kg of mixture is prepared in this way. More specifically, for the compositions according to invention No. 1 and control compositions T2 to T4, all of the compounds under consideration are mixed in the form of granules in a given proportion with the substance PP, also in a given proportion, using a laboratory mixer to form the corresponding composition, before forming each by injection molding.

[0101] A reference composition T5 is also produced.

[0102] [Table 1] EXAMPLES

[0103] Preparation of a molded article consisting of a capsule intended to interact to seal a bottle, obtained by injection molding of the composition of Example 1.

[0104] Compositions No. 1, T2, T3 and T4 are prepared as in Example 1 above.

[0105] The mold is placed into an injection molding press, in this embodiment a Husky machine with or without a pressure sensor. A Netstal Synergy 150 injection molding press may also be used.

[0106] First, at least one test composition, corresponding to composition T5, is injection molded to produce an article based on a polypropylene copolymer sold by LyondellBasell, having the trade name Moplen RP348R-Basell, with an MFI of 25 g / 10 min.

[0107] Injection molding parameters, such as barrel temperature, injection rate, injection pressure, residence time and residence pressure, are established for this test composition.

[0108] The injection time, injection nozzle temperature measurements, and optionally other measurements are recorded.

[0109] Once the injection molding with the test composition has been performed, the injection screw is emptied.

[0110] Composition No. 1 is then sequentially loaded into the hopper of an injection molding press and homogenized in the barrel by the injection screw.

[0111] If appropriate, adjust parameters such as barrel temperature, injection speed, injection pressure, residence time and residence pressure. Record the injection time, nozzle temperature measurements, and optionally other measurements for the test composition, and note the parameters actually used.

[0112] For each of compositions T1, T2, T3 and T4 in turn, injection molding is carried out in the same manner as for composition No. 1, and for each of these compositions, the injection time, the measured values ​​of the nozzle temperature, and optionally other measured values, as well as parameters such as barrel temperature, injection speed, injection pressure, residence time and residence pressure are noted.

[0113] The following Table 2 summarizes selected parameters and measurements for the molding of compositions No. 1, T1, T2, T3, T4 and T5.

[0114] [Table 2]

[0115] Each injection molded article produced according to this method can be recovered to reach room temperature, for example in the open air. Each injection molded article is subsequently packaged for approval testing, if appropriate.

[0116] The above method allows different compositions to be tested and is used to develop injection molding parameters, which is a method for developing a process for the production of an article.

[0117] Such methods may be used without a testing step, i.e., without producing injection molded articles using one or more test compositions. The methods may also not include taking measurements and recording parameters, particularly on systems, especially when constructing the methods and compositions used, and when using the methods to produce injection molded articles at industrial speeds. EXAMPLES

[0118] Characterization of the quality of the injection-molded articles obtained in Example 2 The tests detailed below were performed and the results are presented in Table 3 below.

[0119] [Table 3]

[0120] As is evident from these results, all of the qualities of the article T4 are optimized to the greatest extent possible, and in fact it is the composition according to the invention that produces capsules with even better qualities in terms of the drop test: in contrast to the composition according to the invention, more than 30% of the capsules obtained from composition T3 broke during the drop test.

Claims

1. (a) at least 75% by weight, based on the total weight of the composition, of recycled homopolypropylene, hPP, having a melt flow index of more than 20 grams per 10 minutes (20 g / 10 min), measured at 230° C. under a load of 2.16 kg according to standard ASTM D1238, and (b)(i) a propylene / C2 α-olefin copolymer having at least 75% by weight of units derived from propylene and 10% to 25% by weight of linear or branched C2 alkenyl units, referred to as the “first copolymer”; and (ii) A homogeneous linear or branched ethylene / C copolymer, referred to as the “second copolymer” 4~10 Alpha-Olefin Copolymer 2% to 25% by weight, based on the total weight of the composition, of a mixture of copolymers comprising at least A thermoplastic composition comprising at least A thermoplastic composition, wherein the "second copolymer / first copolymer" mass ratio is between 0.1 and 0.

4.

2. 2. The composition of claim 1, comprising 80% to 95% by weight of recycled hPP based on the total weight.

3. The first copolymer has a viscosity of 0.50 to 0.95 g / cm 3 3. The composition of claim 1 or 2, having a density in the range of:

4. 10. The composition of claim 1, wherein the first copolymer has a melt flow index (according to ASTM D1238, conditions 230°C, 2.16 kg) ranging from 1.5 grams / 10 minutes to 500 grams / 10 minutes.

5. The composition of claim 1 , wherein the first copolymer has at least 80% by weight of units derived from propylene, based on the total weight.

6. 10. The composition of claim 1 comprising at least one propylene / ethylene first copolymer.

7. The composition of claim 1, wherein the second copolymer has an ethylene content of from 50% to 98% by weight.

8. 2. The composition of claim 1, wherein the olefin component of the second copolymer is derived from 1-butene, 1-hexene, and / or 1-octene.

9. 2. The composition of claim 1, wherein the "second copolymer / first copolymer" mass ratio is 0.

2.

10. 2. The composition according to claim 1, comprising from 5% to 15% by weight of the mixture of copolymers relative to its total weight.

11. 10. The composition of claim 1 further comprising a clarifying additive.

12. A molded article obtained by molding the composition according to claim 1 in a mold.

13. 1. A method for the production of a molded article, comprising the steps of: Providing a composition according to claim 1 or preparing such a composition; molding the composition in a mold having the shape of the article; and Recovering the molded article. The method includes at least the steps of:

14. The method of claim 13 further comprising the step of blow molding the shaped article.

Citation Information

Patent Citations

  • Recycled polyolefin resin composition

    JP1996127676A

  • Propylene polymer composition

    JP1997040821A

  • Polypropylene resin composition and container

    JP2001151960A

  • Polymer Composition

    US20130023627A1

  • Polymer composition

    US8426521B2